DEMOGRAPHIC ANALYSIS AND BEHAVIORAL PATTERNS OF DOMESTIC TOURISTS IN THE COVID-19 PANDEMIC ERA: AN INVESTIGATIVE STUDY - Lande, Ni Putu Grace A.; Krisna, I Wayan Duta (Transpublika Publisher, 2023)
This research aims to examine the demographics and behavioral patterns of domestic tourists in Indonesia during the COVID-19 pandemic. The study utilized a descriptive research method with a quantitative approach, employing online questionnaires to collect data from respondents who have traveled within the country since March 20, 2020. The collected data were analyzed to gain insights into the demographic characteristics, travel frequency, travel motivations, modes of transportation, and types of tourist attractions visited by the respondents. The findings revealed that the majority of respondents were aged between 19 and 25, primarily originating from Bali, East Java, and Yogyakarta provinces. The main reasons for travel were family invitations, recreation, and stress relief, with private vehicles being the preferred mode of transportation. In conclusion, this study highlights the impact of the COVID-19 pandemic on tourists' travel intentions and preferences. By understanding the demographics and behavior of tourists, destination managers can develop effective marketing strategies to enhance customer satisfaction and strengthen the competitiveness of tourism destinations in the current pandemic era.